Capabilities of Police Officers in Implementing Traffic Rules and Regulations in Traffic Sector 2 Quirino Highway, Novaliches, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Managing traffic is one of the critical assignments of the police officers of PNP. There areinstances that they encounter a situation where their capabilities as traffic police can be put tothe test. As traffic police, they are responsible for ensuring the safety of road users andpedestrians, monitoring the traffic to identify road users who disobey traffic laws, and issuingtickets as penalties. Also, they are the ones who first respond if there is an accident. Part oftheir job as first respondents in traffic accidents are giving first aid to injured road accidentvictims, searching for injured people to bring them to the hospital immediately, and takingpictures for documentation. It is not possible to prevent problems regarding traffic likevehicular accidents, but with the help of knowledgeable, alert, and skilled traffic police, theseverity of injuries can be prevented or minimized.It was discovered that respondents assessed the capabilities of traffic police based on theirknowledge of how to use different traffic equipment, how traffic police conducted initialaccident assessment upon responding to traffic accidents, and their skills on how they wereable to coordinate multiple vehicles and prioritized the smooth flow of traffic. There were manyfactors that affected the capabilities of police officers in handling traffic, such as the behaviorof road users, weather, technologies, and equipment of traffic police, the area where they areassigned, and their health condition.For further enhancement of the capabilities of police officers in implementing traffic rules andregulations, the government should provide seminars to traffic police in order to enhance theircapabilities about traffic rules and regulations, upgrade their technologies and equipment, andenforce strict traffic laws.
Keywords: Criminology